Technological Innovations and Corporate Performance of Deposit Money Banks in Nigeria - Abdullahi, Sani Rufai; Audu, Friday; Odobi, Ojochogwu David; Ahuoiza, Rahanatu; Sadiq, Hajarat (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
To remain competitive and profitable, deposit money banks need to design, develop, and adopt new processes, products, and technology that ensure greater efficiency and performance. Thus, this study investigates the relationship between technological innovations and corporate performance of deposit money banks in Nigeria. The specific objectives were to determine the effect of automated teller machines (ATM), point of sales (POS), mobile banking (MB), and internet banking (IB) on the corporate performance of deposit money banks in Nigeria measured by earnings per share (EPS). The total population of the study consists of the 33 deposit money banks licensed by the Central Bank of Nigeria (CBN) as of 31st December 2022. The study formulated four hypotheses and used ordinary least squares regression to analyze the data extracted from the annual publication of the Central Bank of Nigeria and audited reports and accounts of deposit money banks for the period 2012 to 2022. The study found that automated teller machines (ATMs), points of sale (POSs), and mobile banking (MB) have a significant and positive effect on earnings per share (EPS) of deposit money banks in Nigeria, while internet banking (IB) has an insignificant negative relationship with earnings per share (EPS) of deposit money banks in Nigeria. The study recommends, among others, that the management of deposit money banks in Nigeria should expand the number of ATM and POS outlets even as they expand their bank branches and minimize their investment in internet banking, as its operation does not contribute positively to corporate performance.